2013
DOI: 10.1371/journal.pone.0080576
|View full text |Cite
|
Sign up to set email alerts
|

TIGAR Is Correlated with Maximal Standardized Uptake Value on FDG-PET and Survival in Non-Small Cell Lung Cancer

Abstract: ObjectiveEvaluation of 18F-FDG uptake value via PET is central to current methods of diagnosis and staging of non-small cell lung cancer (NSCLC) due to its ability to evaluate expression levels of key regulators associated with glucose metabolism in tumor cells. Tp53-induced glycolysis and apoptosis regulator (TIGAR) is an important P53-induced protein that can inhibit glycolysis; however, there have been few clinical studies on its mechanism. Here we have investigated the relationship between TIGAR expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Total RNA was extracted from cells and tissues, and the extracted RNA was reverse transcribed and amplified by qRT-PCR as previously described22. The mRNA levels of the target genes were normalized to GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from cells and tissues, and the extracted RNA was reverse transcribed and amplified by qRT-PCR as previously described22. The mRNA levels of the target genes were normalized to GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…Duan et al (26) reported that p53 expression is the primary predictive factor for SUV max . Zhou et al (27) found a significant difference between SUV max and Tp53-induced glycolysis and apoptosis regulator (TIGAR)’s being positive or negative. On the other hand, Watanabe et al (28) did not find a correlation between p53 alteration and FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This supports a two-compartment model of tumor metabolism. In vivo, TIGAR overexpression has been identified in several solid tumor types, including breast, glioblastoma, and non-small cell lung cancer, and in hematologic malignancies such as AML [66] [67] [68] [69]. TP53 mutations induce TIGAR expression more strongly than wild-type TP53 [63].…”
Section: Tigarmentioning
confidence: 99%